A rare case of genital myiasis in a woman with psychiatric disturbance - Upreti Purnima; Umesh Varshney; Mavish Jahan (Wolters Kluwer Medknow Publications, 2017)
A middle-aged psychiatric woman was brought to the casualty by national health ambulance. The patient was a destitute and had psychiatric illness. Local examination revealed irreducible third-degree uterovaginal prolapse with necrotic ulcerated areas infested with maggots. The patient was managed conservatively with the removal of maggots with 100% turpentine oil, culture-sensitive antibiotics, and local antiseptics. With treatment, the prolapsed mass got free of maggots, the ulcerated areas healed, and prolapsed mass became reducible.